2020
DOI: 10.1177/2158244019900567
|View full text |Cite
|
Sign up to set email alerts
|

Cloak of Invisibility: A Literature Review of Physical Disability in Ghana

Abstract: This literature review surveys the state of current scholarship on physical disability in Ghana. The intention is to identify major themes and opinions relating to the challenges faced by Ghanaians with physical disabilities. After an extensive literature review, the authors selected 21 articles for inclusion based on the criteria that they had to focus on physical disability in a Ghanaian setting. Reviewing the articles revealed that most scholars have focused on the pervasive oppression of Ghanaians with phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Baart and Taaka [35] have found that PwDs do not have sustainable sources of income and yet have higher healthcare needs due to their impairment, and are likely to incur higher cost of medical care. To mitigate the financial burden of healthcare for PwDs in Ghana, Ghana's National Health Insurance Policy 2003 provided a special dispensation for PwDs to register and renew their NHIS cards for free [55,56]. However, some healthcare facilities are said to charge PwDs for services, even those covered under the insurance scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Baart and Taaka [35] have found that PwDs do not have sustainable sources of income and yet have higher healthcare needs due to their impairment, and are likely to incur higher cost of medical care. To mitigate the financial burden of healthcare for PwDs in Ghana, Ghana's National Health Insurance Policy 2003 provided a special dispensation for PwDs to register and renew their NHIS cards for free [55,56]. However, some healthcare facilities are said to charge PwDs for services, even those covered under the insurance scheme.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the financial burden of healthcare for PwDs in Ghana, Ghana's National Health Insurance Policy 2003 provided a special dispensation for PwDs to register and renew their NHIS cards for free. [55,56] However, some healthcare facilities are said to charge PwDs for services, even those covered under the insurance scheme. Meanwhile, some of these PwDs have lost their jobs during the Sars-Cov-2 outbreak and have no means of sustenance except for support from relatives.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…In many countries in Africa, efforts to guarantee the rights of PWDs are hampered by several barriers, some of which are socio-cultural while others are physical. In some of these countries, there is a perception that disability is a sign of a bad omen which calls for a mental and behavioural reorientation (Mfoafo-M'Carthy et al, 2020). There is the medical perspective of disability which is being dealt with by medical prescriptions.…”
Section: Introductionmentioning
confidence: 99%